1996
DOI: 10.1128/jb.178.7.2051-2059.1996
|View full text |Cite
|
Sign up to set email alerts
|

glc locus of Escherichia coli: characterization of genes encoding the subunits of glycolate oxidase and the glc regulator protein

Abstract: The locus glc (min 64.5), associated with the glycolate utilization trait in Escherichia coli, is known to contain glcB, encoding malate synthase G, and the gene(s) needed for glycolate oxidase activity. Subcloning, sequencing, insertion mutagenesis, and expression studies showed five additional genes: glcC and in the other direction glcD, glcE, glcF, and glcG followed by glcB. The gene glcC may encode the glc regulator protein. Consistently a chloramphenicol acetyltransferase insertion mutation abolished both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 34 publications
0
117
0
Order By: Relevance
“…Also, Slr0806 harbors a conserved consensus sequence GXGXXG [supporting information (SI) Fig. S1] thought to serve as a flavin-binding domain (26). In addition to GlcD1, the GlcD complex is comprised of a second dehydrogenase subunit GlcE (26), which is Ϸ42% similar to Slr0806.…”
Section: A Triple Mutant In 3 Branches Of 2pg Metabolism Exhibits An Hcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Slr0806 harbors a conserved consensus sequence GXGXXG [supporting information (SI) Fig. S1] thought to serve as a flavin-binding domain (26). In addition to GlcD1, the GlcD complex is comprised of a second dehydrogenase subunit GlcE (26), which is Ϸ42% similar to Slr0806.…”
Section: A Triple Mutant In 3 Branches Of 2pg Metabolism Exhibits An Hcrmentioning
confidence: 99%
“…S1] thought to serve as a flavin-binding domain (26). In addition to GlcD1, the GlcD complex is comprised of a second dehydrogenase subunit GlcE (26), which is Ϸ42% similar to Slr0806. Also, phylogenetic analysis showed that Slr0806-like proteins from several microorganisms clearly cluster with the GlcD/E-group ( Fig.…”
Section: A Triple Mutant In 3 Branches Of 2pg Metabolism Exhibits An Hcrmentioning
confidence: 99%
“…As the resemblance of WhiH to members of the GntR family is closest in the region corresponding to this motif, WhiH is probably a DNA-binding protein. In most cases in which the functions of the members of the GntR family have been studied, they have shown repressor activity, although at least one member, FadR, can also act as a transcriptional activator (DiRusso et al, 1993), and another (GlcC) is only known to act positively on the expression of target genes (Pellicer et al, 1996). Because sporulation is prevented by mutations in whiH, including a constructed disruption expected to produce a null phenotype, a point mutation in the putative DNA-binding motif, and a frameshift mutation eliminating the C-terminal 47 amino acids, the overall role of WhiH in sporulation is positive; but the repressor activity of many of its homologues suggests the alternative or additional possibility that WhiH could itself be a repressor of another negative regulator that would otherwise prevent development.…”
Section: Whih Is Probably a Transcriptional Regulatormentioning
confidence: 99%
“…Among those members of the family whose physiological role and responsiveness are broadly understood, the closest relatives to WhiH are all E. coli proteins that influence the area of carbon metabolism involving organic acids: GlcC, glycolate (Pellicer et al, 1996); ExuR and UxuR, hexuronate (Robert-Baudouy et al, 1981); FadR, fatty acids (DiRusso et al, 1993); LctR, lactate (Dong et al, 1993); PdhR, pyruvate (Quail et al, 1994). By analogy, WhiH may perhaps be modulated by a specific metabolite, whose concentration changes during development.…”
Section: Whih Is Probably a Transcriptional Regulatormentioning
confidence: 99%
“…The locus glc (67n3 min), associated with glycolate utilization in Escherichia coli, is known to contain glcB, encoding malate synthase G, the genes glcDEF needed for glycolate oxidase activity, and glcG, of unknown function (Molina et al, 1994 ;Pellicer et al, 1996). However, the gcl gene encoding glyoxylate carboligase is not linked to the glc locus and is located at 12 min (Chang et al, 1993).…”
Section: Abbreviationsmentioning
confidence: 99%